Textbook on land law - MacKenzie, Judith-Anne (Oxford University Press, 2002)
Textbook on Land Law guides students through the principles of contemporary land law from a practical perspective. It focuses on the modern law, confining discussion of historical developments to the minimum necessary to understand basic principles and concentrate on the law as it is now.